A adaptação barroca de Dom Casmurro para Capitu: do livro ao corpo na TV - Rosa, Luiza Maria Almeida (2012)
This research is inscribed in the gap between two ends: the eyes of the body and the eyes of the lenses of the cameras in the dialog between literature and body in/of the television. It investigates the relation of the book Dom Casmurro, written by Machado de Assis and published in 1899, and the micro-series Capitu, directed by Luiz Fernando Carvalho and broadcasted by Rede Globo de Televisão, in 2008. The hypothesis that lead this research is that the actors and the director expand the narrative written by Machado de Assis, the melodrama TV repertory and the format of the fiction series through dramaturgical and metaphorical baroque procedures (SARDUY, 1979, CAMPOS, 2001 e PINHEIRO, 2009). The interpretation of the book was based on status of characters that refer to the kind of canonic melodrama, including the clown and the masks of commedia dell'arte. Its choices of repertories and scenarios (TAYLOR, 2003), transformed stereotypes in archetypes, which gave them the allegorical hint (timeless and unlikely) of the micro-series, which is not present in the book. Apart from that, this research tries to draw attention to metaphoric procedures of the body (RENGEL, 2007) in the moderation between book and body in/of the television: the manipulation of a video camera as a human eye and the perception of the environment as with human sensory-motor qualities allowed that the unreliability in the veracity of the protagonist's speech in the book appeared in the micro-series in the form of dark and out of focus images and distorted bodies. In the caricature, the allegorical timeless, the artificialization and articulation of the text of the book with other contexts (parodies), the micro-series gives clues that transforms the narrative of the book by a baroque way. Hence, it stands out in the history of the dramaturgical television (MARTINBARBERO, 2003). The aim to unveil the body as a material of analysis in the studies about communication and culture, this research comes from the epistemology, understanding it as a process of communication in constant dialog with the environment: body as media of itself (KATZ & GREINER, 2005). The theoretical basis to investigate the bond among communication-body-culture is supported by the Bodymedia Theory and the methodology chosen was the bibliographic review to sustain the analysis of corpus and interviews to uphold the analysis about the baroque transfiguration of Dom Casmurro in Capitu